Magnet Analisa Fundamental Di Kalangan Mahasiswa Generasi Z Menjadi Investor GISBEI IAIN Syekh Nurjati Cirebon - Selasi, Dini; Vidiati, Cory; Munajim, Ahmad; Pratama, Gama; Ridwan, Muhammad; Kasnawi, Kasnawic (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
This research is motivated by the development of investors among students in managing finances, namely by investing in Islamic stock investments. This study aims to find out how the fundamental strategy is carried out by students at IAIN Syekh Nurjati Cirebon. The research method used is qualitative research using interviews, observation and qualitative descriptive data analysis techniques. The results of this study are that there are several fundamental techniques used in trading Islamic stocks, namely by looking at news related to the development and performance of the company, the company's financial statements, the use of SOTS and RTI Business applications. The conclusion in this study is that in using fundamental analysis, students will use different strategies and are tailored to their respective investment goals.